A Descriptive Study of Registers Found in Spoken and Written Communication (A Semantic Analysis) - Nurul Hidayah (Register Journal, 2009)
This research is descriptive study of registers found in spoken and written communication. The type of this research is Descriptive Qualitative Research. In this research, the data of the study is register in spoken and written communication that are found in a book entitled "Communicating! Theory and Practice" and from internet. The data can be in the forms of words, phrases and abbreviation. In relation with method of collection data, the writer uses the library method as her instrument. The writer relates it to the study of register in spoken and written communication. The technique of analyzing the data using descriptive method. The types of register in this term will be separated into formal register and informal register, and identify the meaning of register.Keywords: Register; Spoken and Written Communication;  Jargon; Slang; Motherese